Leopard & Silkie : one boy's quest to save the seal pups - Peterson, Brenda, 1950- (Henry Holt and Co., 2012)
"In the Pacific Northwest, concerned volunteers become seal sitters, keeping vigil over the vulnerable baby seals that are left on the shore while their mothers hunt for food. Surviving in the animal kingdom is never easy and this informative picture book gives a first-hand look at what baby seals are up against. With its emphasis on human compassion, this true account teaches children to appreciate the natural world by helping in any way they can. The star of the book is six year old Miles, who organizes his own rescue mission to help the seals survive"--